2016
DOI: 10.1039/c5pp00366k
|View full text |Cite
|
Sign up to set email alerts
|

The internal heavy-atom effect on 3-phenylselanyl and 3-phenyltellanyl BODIPY derivatives studied by transient absorption spectroscopy

Abstract: Three monosubstituted 3-phenylselanyl and 3-phenyltellanyl BODIPY derivatives were synthesized and their spectroscopic properties were characterized and compared to those of iodine and chlorine-atoms containing analogues as well as an unsubstituted BODIPY derivative. The fluorescence quantum yields were found to decrease, whereas the intersystem crossing quantum yields (ΦISC), determined by transient spectroscopy, increased in the order of the H → Cl → Se/I → Te substitution. The maximum ΦISC, found for the 3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
30
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 53 publications
1
30
2
Order By: Relevance
“…On the other hand, the chalcogen-substituted BODIPYs displayed broad emission bands and large Stokes shifts (Dñ = 3692-5128 cm À1 ; Fig. S28-S35, ESI †), fluorescence lifetimes (t f E 3-6 ns) in the same order as those of unsubstituted BODIPYs, 20 and surprisingly high F f values, especially in the case of ditelluro-analogue 7d (18%). BODIPY derivatives possessing large Stokes shifts based on geometrical changes upon excitation, 39 intramolecular charge transfer (ICT), 40 or extension of the chromophore 41 have already been reported.…”
mentioning
confidence: 96%
See 4 more Smart Citations
“…On the other hand, the chalcogen-substituted BODIPYs displayed broad emission bands and large Stokes shifts (Dñ = 3692-5128 cm À1 ; Fig. S28-S35, ESI †), fluorescence lifetimes (t f E 3-6 ns) in the same order as those of unsubstituted BODIPYs, 20 and surprisingly high F f values, especially in the case of ditelluro-analogue 7d (18%). BODIPY derivatives possessing large Stokes shifts based on geometrical changes upon excitation, 39 intramolecular charge transfer (ICT), 40 or extension of the chromophore 41 have already been reported.…”
mentioning
confidence: 96%
“…We recently reported on the synthesis of several 3-chalcogen substituted BODIPYs, which exhibit intersystem crossing (ISC) quantum yields comparable to those of iodo-analogues. 20 Due to their high photostability and low toxicity, chalcogen-substituted BODIPYs are promising triplet sensitizers 21 which can be used in photodynamic therapy 22 or triplet-triplet annihilation upconversion. 4,23 Ortiz and coworkers have recently demonstrated that heavyatom substituents at the 2,6-positions have the highest impact on ISC quantum yields.…”
mentioning
confidence: 99%
See 3 more Smart Citations